Study of uniformity of elongated plasma channels formed in gas puff targets using extreme ultraviolet and soft X-ray radiation. (17th April 2015) - Wachulak, P.W.; Bartnik, A.; Jarocki, R.; Fok, T.; Węgrzyński, Ł.; Kostecki, J.; Szczurek, M.; Fiedorowicz, H.
Abstract The results of formation of elongated krypton/helium plasma channels are presented. Two laser pulses were used: one to produce plasma channels and the second one for conversion to soft X rays. The soft X-ray radiation was in turn used for backlighting the channels and their visualization. The study of their formation and uniformity was performed using a combination of soft X-ray shadowgraphy and pinhole camera imaging. The plasma channels, with various lengths and various densities, were visualized and the results of their characterization are presented. Using moderate laser pulse energy quite uniform channels, up to 9 mm in length, were demonstrated.